Selecting Information Sources in Times of Crisis - Bastari, Andi Amiratania (UI Scholars Hub, 2020)
The Indonesian government has employed communication strategies such as leveraging new media and big data to provide its citizens with information during the Covid-19 global pandemic. Previous research has shown that these are some tools that were used by digital PR practitioners during a crisis. However, it is said that research on usage of new media has been focused on the organizational perspective. This article conducted an exploratory study on how and why users select certain forms of new media to search for information. An in-depth interview with three informants was done to gain a societal perspective. Uses and gratifications theory, including its development due to the advancement Of technology in Industry 4.0, served as a framework to analyze the data gathered from the interview. The results showed that all three informants tend to use alternative new media because of the gratification it provides, instead of Gugus Tugas’s official website. This article contributes to the literature on new media user behavior in selecting information sources in times of crisis. It also provides practical and theoretical insights for future studies. Pemerintah Indonesia telah menggunakan strategi komunikasi seperti pemanfaatan media baru dan data besar untuk memberikan informasi kepada warga selama menghadapi pandemi global Covid-19. Penelitian sebelumnya telah menunjukkan bahwa ini adalah beberapa alat yang digunakan oleh praktisi PR digital selama krisis. Namun demikian, penelitian tentang penggunaan media baru lebih banyak difokuskan pada perspektif organisasi. Artikel ini melakukan studi eksplorasi tentang bagaimana dan mengapa pengguna memilih bentuk media baru tertentu untuk mencari informasi. Wawancara mendalam dengan tiga informan dilakukan untuk mendapatkan perspektif dari sisi masyarakat. Teori Uses and Gratifications, termasuk perkembangannya akibat kemajuan teknologi Industri 4.0, berfungsi sebagai kerangka kerja untuk menganalisis data yang telah dikumpulkan dalam wawancara. Hasil penelitian menunjukkan bahwa ketiga informan cenderung menggunakan media baru alternatif karena lebih memuaskan daripada situs resmi Gugus Tugas. Artikel ini berkontribusi pada literatur tentang perilaku pengguna media baru dalam memilih sumber informasi di saat krisis. Artikel ini juga memberikan masukan praktikal dan teoritis untuk penelitian di masa depan.